Resistance is futile: RNA-sequencing reveals differing responses to bat fungal pathogen in Nearctic Myotis lucifugus and Palearctic Myotis myotis - Thomas M. Lilley; Jenni M. Prokkola; Anna S. Blomberg; Steve Paterson; Joseph S. Johnson; Gregory G. Turner; Tomáš Bartonička; Erik Bachorec; DeeAnn M. Reeder; Kenneth A. Field (Oecologia, 2019)
Resistance and tolerance allow organisms to cope with potentially life-threatening pathogens. Recently introduced pathogens initially induce resistance responses, but natural selection favors the development of tolerance, allowing for a commensal relationship to evolve. Mycosis by Pseudogymnoascus destructans , causing white-nose syndrome (WNS) in Nearctic hibernating bats, has resulted in population declines since 2006. The pathogen, which spread from Europe, has infected species of Palearctic Myotis for a longer period. We compared ecologically relevant responses to the fungal infection in the susceptible Nearctic M. lucifugus and less susceptible Palearctic M. myotis , to uncover factors contributing to survival differences in the two species. Samples were collected from euthermic bats during arousal from hibernation, a naturally occurring phenomenon, during which transcriptional responses are activated. We compared the whole-transcriptome responses in wild bats infected with P. destructans hibernating in their natural habitat. Our results show dramatically different local transcriptional responses to the pathogen between uninfected and infected samples from the two species. Whereas we found 1526 significantly upregulated or downregulated transcripts in infected M. lucifugus , only one transcript was downregulated in M. myotis . The upregulated response pathways in M. lucifugus include immune cell activation and migration, and inflammatory pathways, indicative of an unsuccessful attempt to resist the infection. In contrast, M. myotis appears to tolerate P. destructans infection by not activating a transcriptional response. These host-microbe interactions determine pathology, contributing to WNS susceptibility, or commensalism, promoting tolerance to fungal colonization during hibernation that favors survival. Graphic abstract